Combined Electric and Acoustic Stimulation With Hearing Preservation: Effect of Cochlear Implant Low-Frequency Cutoff on Speech Understanding and Perceived Listening Difficulty. Issue 5 (September 2017) - Gifford, René H.; Davis, Timothy J.; Sunderhaus, Linsey W.; Menapace, Christine; Buck, Barbara; Crosson, Jillian; O'Neill, Lori; Beiter, Anne; Segel, Phil
Abstract : Objective: The primary objective of this study was to assess the effect of electric and acoustic overlap for speech understanding in typical listening conditions using semidiffuse noise. Design: This study used a within-subjects, repeated measures design including 11 experienced adult implant recipients (13 ears) with functional residual hearing in the implanted and nonimplanted ear. The aided acoustic bandwidth was fixed and the low-frequency cutoff for the cochlear implant (CI) was varied systematically. Assessments were completed in the R-SPACE sound-simulation system which includes a semidiffuse restaurant noise originating from eight loudspeakers placed circumferentially about the subject's head. AzBio sentences were presented at 67 dBA with signal to noise ratio varying between +10 and 0 dB determined individually to yield approximately 50 to 60% correct for the CI-alone condition with full CI bandwidth. Listening conditions for all subjects included CI alone, bimodal (CI + contralateral hearing aid), and bilateral-aided electric and acoustic stimulation (EAS; CI + bilateral hearing aid). Low-frequency cutoffs both below and above the original "clinical software recommendation" frequency were tested for all patients, in all conditions. Subjects estimated listening difficulty for all conditions using listener ratings based on a visual analog scale. Results: Three primary findings were that (1) there was statistically significant benefit of preserved acoustic hearing in the implanted ear for most overlap conditions, (2) the default clinical software recommendation rarely yielded the highest level of speech recognition (1 of 13 ears), and (3) greater EAS overlap than that provided by the clinical recommendation yielded significant improvements in speech understanding. Conclusions: For standard-electrode CI recipients with preserved hearing, spectral overlap of acoustic and electric stimuli yielded significantly better speech understanding and less listening effort in a laboratory-based, restaurant-noise simulation. In conclusion, EAS patients may derive more benefit from greater acoustic and electric overlap than given in current software fitting recommendations, which are based solely on audiometric threshold. These data have larger scientific implications, as previous studies may not have assessed outcomes with optimized EAS parameters, thereby underestimating the benefit afforded by hearing preservation. Abstract : Supplemental Digital Content is available in the text.